Food safety: The biggest development challenge you’ve never heard of - Global Alliance for Improved Nutrition (2023)
Delia Grace Randolph, the world’s leading researcher on food safety in traditional markets makes a case for investment in food safety. Impacting billions of people directly and indirectly every year, foodborne disease (FBD) is a low-hanging fruit in the development agenda to improve the quality of life in LMICs. Feed The Future’s EatSafe: Evidence and Action Towards Safe, Nutritious Food (EatSafe), highlights how the problem is immense, tractable, and has been neglected for decades by governments and international donors. Minimizing FBD in traditional markets not only prevents people from getting sick, but it helps seize the full potential of investments in nutrition, health, education, and financial independence. Traditional markets are the main source of nutrition for billions of people around the globe. They are often the main source of income for women and a hub of communal life. But with development dollars largely going to agriculture and nutrition programs, these market vendors have been neglected by the donors for decades. Traditional market vendors often lack the necessary infrastructure, food handling skills, and incentives to ensure that the food they sell is safe to consume. As a too common result, the available perishable, and highly nutritious foods, like meat, GLV, eggs, and dairy, often contain pathogens, such as salmonella, that compromise human health--particularly in young children, the elderly population, and the immunosuppressed.